Self-limiting Spontaneous Isolated Celiac Artery Dissection: A Case Report. (2015) - Morzycki, A.D.; Casey, P.; Lee, M.
Abstract : Introduction: Isolated dissection of the celiac artery is rare, with less then 100 cases reported to date. Although some patients present with epigastric pain and tenderness, many cases are asymptomatic and found incidentally on CT. The appropriate management of isolated celiac artery dissections is unclear. This report illustrates an observational approach to a symptomatic case of isolated celiac artery dissection. Report: A 55-year-old Caucassian male presented to the emergency department with epigastric pain. His Initial CT revealed possible celiac artery dissection with associated intramural hematoma. Due to continued pain, a subsequent CTA was ordered. This scan showed progression of the intramural hematoma to near occlusion of the hepatic artery. Despite this, there were no signs of ischemic hepatitis as indicated by normal levels of liver transaminases. There was also no evidence to suggest propagation of the dissection or pseudo-aneurysm formation. We therefore choose a conservative and observational approach to this isolated celiac artery dissection. His dissection was managed with ASA and metoprolol, and he was discharged after 1 week of observation. 3 week follow-up CTA showed spontaneous resolution of the intramural hematoma and improved patency of the hepatic artery. There was no change at 3 months follow-up. Conclusion: This case highlights that an observational approach to cases of isolated celiac artery dissection may be indicated if there is no evident end organ disease or malperfusion. Highlights: We herein present a case of spontaneous isolated celiac artery dissection. An observational approach to this dissection was taken. This dissection was well managed with ASA and metoprolol. This isolated disease resolved organically and did not require endovascular or surgical intervention.